Sellar Region Lesions and Intracranial Aneurysms in the Era of Endoscopic Endonasal Approach - Yan, Siyu; Liu, Yifan; Liu, Chang; Yang, Li; Qin, Yun; Liu, Ran; Wang, Shan; Li, Xue; Yang, Wenjie; Ma, Lu; You, Chao; Zhou, Liangxue; et al. (Frontiers in Endocrinology, 2021)
In the clinical practice of neurosurgery, the endoscopic endonasal approach (EEA) has been the mainstream approach in the management of sellar region diseases. However, clinicians have come to realize that EEA procedure is associated with intraoperative hemorrhage. Due to the limited surgical field and poor proximal control under endoscope, massive hemorrhage always leads to severe complication or even perioperative death. Previously, intraoperative hemorrhage used to be attributed to endoscopic intervention of cavernous sinus or internal carotid artery, but our recent understanding of EEA indicated that preoperatively complicated intracranial aneurysms (IAs) may play a role. In this article, we retrospectively reviewed the baseline characteristics, treatment strategy, pathology, intraoperative findings, as well as radiological profiles of sellar region lesions complicated with IAs. With the focus put on the high comorbidity rate of sellar region lesions and IAs, we did further statistical analysis to sketch the outline of this coexisting circumstance and to emphasize the importance of computed tomography angiography (CTA) as routine EEA preoperative examination. Thorough patient-surgeon communication should be proceeded before the formulation of an individualized treatment strategy.